Analysis And Performance Comparison of Microwave And WiFi 802.11ac Based Backhaul For Long Term Evolution Network In Urban Area - Nida Nurvira; Anggun Fitrian Isnawati; Achmad Rizal Danisya (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2020)
Increasing user requirements for LTE networks, data traffic from eNodeB to core network is also increases, therefore, the recommended solution for meeting this high data traffic is to use a backhaul network design. Backhaul is the path or network used to connect eNodeB with the core network. In this research, backhaul technology used is wi-fi 802.11ac backhaul and microwave backhaul. In this study begins by collecting existing data, then perform capacity calculations to find out the number of eNodeB needed and to find out the capacity of the backhaul links to be designed, then determine the antenna height to achieve LOS conditions, then calculate the desired performance standards and calculate the backhaul network link budget on microwave and wi-fi technologies. Based on the calculation results in terms of capacity, the total user target is 90,167 users and has a throughput capacity per eNodeB of 61 Mbps. In the link-capacity calculation, the total link capacity is 427 Mbps. From the simulation results that using microwave technology, the average RSL value is -30.90 dBm, the value meets the -57 dBm threshold standard and the value of availability does not meet the standard of 99.999% because the average value obtained is 99.998095%. Whereas for wi-fi technology, the average RSL value is -39.24 dBm and meet the -72 dBm threshold standard, for the average availability value meets 99.999% standard, with a value of 100%. From the results of the two technologies, can be conclude that the wi-fi technology is more suitable for the use of backhaul network design in Ciputat Sub-district.